Atypical Presentation of Disseminated Intravascular Coagulation with Synchronous Peripheral Venous Thromboembolism and Arterial Gangrene in a Pancreatic Cancer Patient: A Case Report - Kus, Tulay; Kalender, Mehmet Emin; Aktas, Gokmen; Suner, Ali; Camci, Celaletdin (JOP. Journal of the Pancreas, 2015)
Context Cancer is a prothrombotic state and anticancer therapies are often complicated by vascular events. The risk of developing thromboembolic events is substantially increased in patients with pancreatic cancer. One possible presentation of vascular events in pancreatic cancer is disseminated intravascular coagulation (DIC). Case report In our case a patient with a diagnosis of pancreatic cancer initially presented with thrombosis and received low molecular weight heparin (LMWH) in addition to standard chemotherapy regimen. He was thought to have DIC by assessment of clinical and laboratory findings. Conclusion Clinically, thrombosis was first located in the left femoral vein and encountered at right femoral artery after three weeks. This pattern was an unusual presentation of DIC. Subclinical DIC is common in patients presenting with pancreatic cancer and is considered a ‘poor’ prognostic factor. Acute DIC, on the other hand is a potentially mortal condition. Image: The legs 7 weeks after diagnosis.